2012
DOI: 10.1002/cncr.27814
|View full text |Cite
|
Sign up to set email alerts
|

Impact of oncology‐related direct‐to‐consumer advertising

Abstract: BACKGROUND:Little is known about the impact of direct-to-consumer advertising (DTCA) on appropriate versus inappropriate prescribing. Aromatase inhibitor (AI) therapy for breast cancer provides an ideal paradigm for studying this issue, because AIs have been the focus of substantial DTCA, and because they should only be used in postmenopausal women, age can serve as a simple surrogate marker of appropriateness. METHODS: Data regarding national DTCA spending for the AIs were obtained from TNS Multimedia; hormon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 89 publications
0
7
0
Order By: Relevance
“…On one hand, these results lend support to an argument by proponents that DTCA indirectly benefits patients by encouraging broader health information seeking behaviors that may in turn lead to more appropriate cancer care [50]. As a result, policies governing DTCA should be relaxed to promote greater dissemination of valuable health information to consumers [10].…”
Section: Discussionmentioning
confidence: 69%
“…On one hand, these results lend support to an argument by proponents that DTCA indirectly benefits patients by encouraging broader health information seeking behaviors that may in turn lead to more appropriate cancer care [50]. As a result, policies governing DTCA should be relaxed to promote greater dissemination of valuable health information to consumers [10].…”
Section: Discussionmentioning
confidence: 69%
“…Another study reported that overall spending on DTCA for aromatase inhibitors (a class of oral medications for reducing the risk of breast cancer recurrence) is associated with a small but significant increase in appropriate prescriptions for women diagnosed with breast cancer (i.e., postmenopausal women) at the population level. Conversely, ad spending is not associated with an increase in inappropriate prescriptions (i.e., premenopausal women) (Abel et al, 2013). …”
Section: Overview Of Dtca Exposure and Its Effectsmentioning
confidence: 99%
“…Such estimates are imprecise measures of exposure both because they are geographically aggregated and also because expenditures may not accurately reflect the actual exposure of individuals to such messaging. 6,7,10 In addition, many prior studies have been unable to account for physician-targeted promotion, yet the use of samples and office-based detailing is common and may be heavily correlated with consumer-targeted promotion. 5,7,11 Finally, contextual factors such as health care density and socioeconomic status may also be influential in driving the outcomes of interest, yet studies of the effects of DTCA have not consistently accounted for these factors.…”
Section: Introductionmentioning
confidence: 99%
“…6,7,10 In addition, many prior studies have been unable to account for physician-targeted promotion, yet the use of samples and office-based detailing is common and may be heavily correlated with consumer-targeted promotion. 5,7,11 Finally, contextual factors such as health care density and socioeconomic status may also be influential in driving the outcomes of interest, yet studies of the effects of DTCA have not consistently accounted for these factors. 57,10 In order to address these limitations, we examined the association between statin advertising and both non-drug and prescription drug health care utilization for each of the top 75 designated market areas (DMAs) in the United States.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation